(untitled) (Journal of Asian Geography, 2024)
The main sources of metal pollution are identified and the potential toxicity of dredged materials on agricultural land is estimated by sediment investigations. Here, we investigated chemical composition of sediment in Bernam catchment. Bernam river catchment has been engulfed by certain anthropogenic activities such as urbanization, illicit logging, farming. Serious concerns have been raised by stakeholders and local people because of the level of pollution due to the release of chemicals and sediments into water bodies by these human activities. Chemical composition elements such as Iron, Aluminium, Copper, Total Organic Carbon, Zinc, Potassium, Calcium, Magnesium, Sodium, Chromium, Cobalt, Nikel, Arsenic and Cadmium have been detected in this study. Characterising potential sediment sources by their diagnostic chemical and physical properties and contrasting them with the properties of transported fluvial material are key components of the methodology used to determine the source of the sediment. The methodology focuses on fluvial sampling techniques used in sediment tracing studies and their suitability for various hydrologic and morphologic river conditions. Based on cluster analysis, there are three cluster of group classification in this catchment. From a management standpoint, determining the sediment is essential to putting into practice the right controls to prevent sediment mobilisation and the ensuing siltation of river channels in the sensitive areas.